Esophageal Cancer in Canada: Trends according to Morphology and Anatomical Location - Michael C Otterstatter; James D Brierley; Prithwish De; Larry F Ellison; Maureen MacIntyre; Loraine D Marrett; Robert Semenciw; Hannah K Weir; for the Canadian Cancer Statistics Steering Committee (Canadian Journal of Gastroenterology)
BACKGROUND: Esophageal adenocarcinoma has one of the fastest rising incidence rates and one of the lowest survival rates of any cancer type in the Western world. However, in many countries, trends in esophageal cancer differ according to tumour morphology and anatomical location. In Canada, incidence and survival trends for esophageal cancer subtypes are poorly known.